Synergy between energy technologies and CO2 emitting goods trade in leading energy-intensive economies: proactive or counterproductive governance? - Md. Monirul Islam; Md. Idris Ali; Md. Moniruzzaman (Sustainable Futures)
The trade of CO2 emissions encompasses the balance of exports and imports related to goods that contribute to carbon dioxide emissions. However, energy technologies, whether clean or carbon-intensive, significantly influence this trade. We investigate the impact of decomposed energy technologies, both clean and fossil fuel-based, on the export of CO2 emitting goods from the world’s top energy-intensive countries during the period from 1990 to 2022. Given the heterogeneity and endogeneity inherent in the data, we employ quantiles via moments and high-dimensional fixed effects linear regression techniques, respectively. Our findings reveal a monotonic positive impact of clean energy technologies in reducing the export of goods associated with CO2 emissions. In contrast, fossil fuel technologies tend to increase the export of such goods. Interestingly, the interaction between sustainable and fossil fuel technologies contributes to a reduction in these exports, highlighting the significant role of sustainable technological development. However, when considering the interaction between both types of technologies (clean and fossil fuel) and governance practices, we observe an increase in the exports of goods associated with CO2 emissions. This underscores the substantial influence of governance practices on increasing the export of these goods. Our results suggest that advancing sustainable energy technologies and proactive governance can lessen the export of CO2-emitting goods, promoting environmental safety.